Comprehensive two-dimensional liquid chromatography with parallel gradients for separation of phenolic and flavone antioxidants - Cacciola, F; Jandera, P; Hajdú, Z; Cesla, P; Mondello, L (Journal of chromatography. A, 2007)
Various combinations of PEG-silica, phenyl-silica and C18 columns in a single-column or serial (tandem) arrangement in the first dimension and a monolithic Chromolith column in the second dimension were tested for comprehensive two-dimensional (2D) LCxLC separation of phenolic and flavone natural antioxidants. The combinations of different stationary phase chemistries provided low selectivity correlations between the first-dimension and the second-dimension separation systems. Improvement in system orthogonality, bandwidths suppression, more regular band distribution over the whole 2D retention plane and increased peak capacity in different 2D setups was achieved by using gradients with matching profiles running in parallel in the two dimensions over the whole 2D separation time range. Instead of two sampling loops, two alternating trapping XTerra columns were used for sample fraction transfer from the first-dimension column to the second dimension. Stronger retention on the XTerra columns in comparison to PEG-silica or phenyl-silica columns in the first dimension allowed using focusing of sample fractions in narrow zones on the top of a trapping column and back-flushing into the second dimension in a very low volume of the mobile phase. This fraction transfer modulation provided significant bandwidth suppression in the second dimension. 2D systems with optimized stationary phase selectivity, parallel gradients and fraction transfer modulation using two trapping columns were applied for the analysis of natural antioxidants in beer and wine samples.
Keywords: Antioxidants; fenoly; Chromatography, Liquid; Flavones; senzitivita a specificita; Sensitivity and Specificity; antioxidancia; chromatografie kapalinová; Phenols; flavony